2021
DOI: 10.1089/ars.2020.8218
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica BcfH Is a Trimeric Thioredoxin-Like Bifunctional Enzyme with Both Thiol Oxidase and Disulfide Isomerase Activities

Abstract: Aims: Thioredoxin (TRX)-fold proteins are ubiquitous in nature. This redox scaffold has evolved to enable a variety of functions, including redox regulation, protein folding, and oxidative stress defense. In bacteria, the TRX-like disulfide bond (Dsb) family mediates the oxidative folding of multiple proteins required for fitness and pathogenic potential. Conventionally, Dsb proteins have specific redox functions with monomeric and dimeric Dsbs exclusively catalyzing thiol oxidation and disulfide isomerization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…Moreover, the putative N-terminal oligomerization domains (50 residues after the signal sequence of both PmScsC and CcScsC) share more than 30% sequence identity. Comparison of the N-terminal sequence of CcScsC with those of other bacterial oxidoreductases that have been reported to be trimeric [S. Typhimurium BcfH (StBcfH;Subedi et al, 2021) and Wolbachia pipientis -DsbA2 (WpDsbA2; Walden et al, 2019)] further highlights similarities between the trimeric proteins and CcScsC (Fig. 1c).…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, the putative N-terminal oligomerization domains (50 residues after the signal sequence of both PmScsC and CcScsC) share more than 30% sequence identity. Comparison of the N-terminal sequence of CcScsC with those of other bacterial oxidoreductases that have been reported to be trimeric [S. Typhimurium BcfH (StBcfH;Subedi et al, 2021) and Wolbachia pipientis -DsbA2 (WpDsbA2; Walden et al, 2019)] further highlights similarities between the trimeric proteins and CcScsC (Fig. 1c).…”
Section: Introductionmentioning
confidence: 79%
“…It has been suggested that this segment allows the three catalytic domains of PmScsC to explore a wide range of conformations during the refolding of bound misfolded substrates (Furlong et al, 2017(Furlong et al, , 2019. Trimeric StBcfH adopts at least two different conformations (found in the crystal asymmetric unit), and like eukaryotic protein disulfide isomerases (Soares Moretti & Martins Laurindo, 2017) StBcfH is both a dithiol oxidase and a disulfide isomerase (Subedi et al, 2021). For trimeric WpDsbA2, SAXS data analysis suggests that the N-terminal trimerization domain is rigid and may contribute to disulfide isomerase activity simply by bringing three DsbA-like domains into close proximity (Walden et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include uropathogenic E. coli (UPEC) strain CFT073 that possesses a canonical DsbA and an accessory DsbA homologue DsbL [19] , [54] or the widely distributed facultative anaerobe Shewanella oneidensis , which has a complex DSB machinery with four DsbA (DsbA1-4) and two DsbB (DsbB1-2) homologues [59] . Similarly, Salmonella enterica ( Se ) encodes four DsbA-like proteins [41] , namely DsbA, DsbL, SrgA [42] , a virulence plasmid-encoded DsbA-like protein, and ScsC [60] , [61] , a DsbA-like protein that protects against copper toxicity [57] , [62] . These Salmonella DsbA paralogues were found to share low sequence identity along with significant differences in their surface features and redox properties [41] .…”
Section: The Thiol Oxidase Dsba From E Coli K-12mentioning
confidence: 99%
“…Interestingly, BcfH has been shown to form a trimeric structure, exceptionally uncommon among the thioredoxin superfamily members. Additionally, BcfH has both thiol oxidase and disulfide isomerase activities contributing to Salmonella fimbrial biogenesis [57] .…”
Section: The Thiol Oxidase Dsba From E Coli K-12mentioning
confidence: 99%